Religious coping, social support, and resilience: a comparison of older and younger adults during the COVID-19 pandemic in the United States - Liu, Stephanie M. (Journal of religion, spirituality & aging, 2025)
This study examined the psychological impact of the COVID-19 pandemic and resilience promoting factors in older (65+ years) and younger adults (20–50 years). In September 2020, 304 participants completed an online questionnaire assessing religious coping, social support, resilience, and mental health. Despite no age differences for resilience, younger adults endorsed more psychopathology. Multiple linear regression analyses revealed stress and social support as predictors of resilience for both cohorts. For younger adults, who were more religious, positive religious coping also predicted resilience. These insights can inform interventions targeting stress and promoting social support and positive religious coping in times of crisis.